Requirements for Digital Transformation in Schools of the Second Cycle of Basic Education in Lattakia City from the point of view of Teachers in it "Field Study" - عجيب يحيى; خضر علي; مطيعة أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to identify the requirements of digital transformation in the schools of the second cycle of basic education in Lattakia city from the point of view of teachers in it, and to know the differences between the answers of the members of the research sample with regard to the requirements of digital transformation according to the following variables (scientific and educational qualification, and training courses), and to achieve the objectives of the research, the researcher adopted the descriptive approach, and used a questionnaire consisting of (48) phrases, It was applied to the research sample of teachers of the second cycle in the schools of Lattakia city, which numbered (251) teachers. The results of the research showed that the requirements of digital transformation in the schools of the second cycle of basic education in Lattakia city, according to the teachers’ estimation, were high, and the results showed that there was a statistically significant difference between the average scores of teachers of the second cycle of basic education in Lattakia city about their appreciation of the importance of digital transformation requirements in their schools according to the variable of training courses in the field of technology, in favor of teachers who underwent training courses, while there were no statistically significant differences between the average scores of teachers according to the variable Scientific and educational qualification. The research made many recommendations, the most important of which are: qualifying human cadres in the field of education, including administrators, teachers and learners on educational technology tools, increasing the awareness of teachers of basic education schools of the importance of applying digital learning, in addition to providing a school physical structure for the application of digital education in schools